Risk as a process: a history informed hazard planning approach applied to the 2018 post-fire debris flows, Montecito, California - Serra-Llobet, Anna; Radke, John; Kondolf, G. Mathias; Gurrola, Larry; Rogers, J. David; Lindbergh, Sarah; Douvinet, Johnny (Frontiers in Environmental Science, 2023)
Historical information about floods is not commonly used in the US to inform land use planning decisions. Rather, the current approach to managing floods is based on static maps derived from computer simulations of the area inundated by floods of specified return intervals. These maps provide some information about flood hazard, but they do not reflect the underlying processes involved in creating a flood disaster, which typically include increased exposure due to building on flood-prone land, nor do they account for the greater hazard resulting from wildfire. We developed and applied an approach to analyze how exposure has evolved in flood hazard zones in Montecito, California, an area devastated by post-fire debris flows in January 2018. By combining historical flood records of the past 200 years, human development records of the past 100 years, and geomorphological understanding of debris flow generation processes, this approach allows us to look at risk as a dynamic process influenced by physical and human factors, instead of a static map. Results show that floods after fires, in particular debris flows and debris laden floods, are very common in Montecito (15 events in the last 200 years), and that despite policies discouraging developments in hazard areas, developments in hazard zones have increased substantially since Montecito joined the National Flood Insurance Program in 1979. We also highlight the limitation of using conventional Flood Insurance Rate Maps (FIRMs) to manage land use in alluvial fan areas such as Montecito. The knowledge produced in this project can help Montecito residents better understand how they came to be vulnerable to floods and identify action they are taking now that might increase or reduce their vulnerability to the next big flood. This science-history-centric approach to understand hazard and exposure evolution using geographic information systems (GIS) and historical records, is generalizable to other communities seeking to better understand the nature of the hazard they are exposed to and some of the root causes of their vulnerabilities, in other words, both the natural and social processes producing disasters.